2020
DOI: 10.3390/ijerph17020600
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Loneliness and Health Related Quality of Life (HR-QoL) among Community-Dwelling Older Citizens

Abstract: Background: This study aimed to assess the association between loneliness and Health-Related Quality of Life (HR-QoL) among community-dwelling older citizens in five European countries. We characterize loneliness broadly from an emotional and social perspective. Methods: This cross-sectional study measured loneliness with the 6-item De Jong Gierveld Loneliness Scale and HR-QoL with the 12-Item Short-Form Health Survey. The association between loneliness and HR-QoL was examined using multivariable linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
5
29
4
4
Order By: Relevance
“…One recent promising development is an analysis using both the De Jong Gierveld scale and the 12-Item Short Form Health Survey used in generating SF-6D scores. This study reported a significant inverse association between increasing loneliness in older people in five European countries and their physical and mental quality of life [61]. Further work could be undertaken to assess how these associations impact on utility weights used to calculate quality adjusted life years.…”
Section: Discussionmentioning
confidence: 79%
“…One recent promising development is an analysis using both the De Jong Gierveld scale and the 12-Item Short Form Health Survey used in generating SF-6D scores. This study reported a significant inverse association between increasing loneliness in older people in five European countries and their physical and mental quality of life [61]. Further work could be undertaken to assess how these associations impact on utility weights used to calculate quality adjusted life years.…”
Section: Discussionmentioning
confidence: 79%
“…Most of the research was conducted in European countries [7, 25, 39-59, 72, 73] with four from the USA [64][65][66][67], two from each of Israel [60,61] and New Zealand [19,62] and single studies from Singapore [68] and Australia [63]. Four studies provided estimates of prevalence across a large proportion of Europe [69][70][71]73]. Living circumstances were reported in seven studies; people living in institutions were included in four studies [25,39,49,50], excluded in three [46,52,61] and no data available from the remainder.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that loneliness is significantly associated with functional decline among the aged [27][28][29]. A recent study that also used the De Jong Gierveld loneliness scale found significant associations between loneliness and physical and mental functioning in an ageing population [30]. In addition, loneliness was negatively correlated with measures of optimism in another cross-sectional study [56].…”
Section: Comparison With Previous Researchmentioning
confidence: 90%
“…Research has shown that loneliness is significantly associated with functional decline among the aged [27][28][29]. A recent study found significant associations between loneliness and physical and mental functioning in an ageing population [30]. De Jong Gierveld et al [31,32] developed a popular loneliness scale and conceptualized loneliness as "an individual's subjective, cognitive evaluation of his or her social participation, or social isolation, against the standards held for optimal embeddedness in a social network" [31].…”
Section: Introductionmentioning
confidence: 99%